PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI NON PNS DI DINAS PENDIDIKAN PROVINSI JAWA BARAT - Yosa Jessica Nabila (Universitas Pendidikan Indonesia, 2021)
This research aims to know the influence of job satisfaction on organizational commitment of non-civil servant employees in The West Java Provincial Departement Of Education. The method used in this research was a descriptive method with a quantitative approach. The data collection technique used was questionnaire that distributed to 83 research respondents. The WMS (Weight Mean Score) calculation result shows that of both variable X and variable Y is at good category. The correlation coefficient between Job Satisfaction and Organizational Commitment obtained a score of 0.644, which was included in the